Multifaceted Interactions Between Endophytes and Plant: Developments and Prospects - Khare, Ekta; Mishra, Jitendra; Arora, Naveen Kumar (Frontiers in Microbiology, 2018)
Microbial endophytes are present in all known plant species. The ability to enter and thrive in the plant tissues makes endophytes unique, showing multidimensional interactions within the host plant. Several vital activities of the host plant are known to be influenced by the presence of endophytes. They can promote plant growth, elicit defense response against pathogen attack, and can act as remediators of abiotic stresses. To date, most of the research has been done assuming that the interaction of endophytes with the host plant is similar to the plant growth-promoting (PGP) microbes present in the rhizosphere. However, a new appreciation of the difference of the rhizosphere environment from that of internal plant tissues is gaining attention. It would be interesting to explore the impact of endosymbionts on the host’s gene expression, metabolism, and other physiological aspects essential in conferring resistance against biotic and abiotic stresses. A more intriguing and inexplicable issue with many endophytes that has to be critically evaluated is their ability to produce host metabolites, which can be harnessed on a large scale for potential use in diverse areas. In this review, we discuss the concept of endophytism, looking into the latest insights related to the multifarious interactions beneficial for the host plant and exploring the importance of these associations in agriculture and the environment and in other vital aspects such as human health.